Agathokakological Aspect of Alcohol Advertising in Newspapers - Karki, Yajur (International Journal of Social Sciences and Management, 2021)
Nepal has a perennial history with the culture of alcohol and it is mostly seen as a form of social capital. Alcohol usage has been inextricable with local cultures, i.e., festivals. The current study aims to investigate aspects of alcohol advertising in newspapers using content analysis. The study focuses on unraveling the ideologies of liquor advertisers in boosting alcohol promotion mostly among the youth. Ostensibly, the boosterism of alcohol advertisements has been concomitant in an attempt to establish it as a mass culture. Consumerism remains the central theme of global contemporary societies and the fundamentals of capitalism are characterized by oligopolistic standards. Facets of such attempt to create a culture revolving around alcohol by injecting messages through advertisements to specific age groups. Forty random private newspapers and twenty state newspapers are taken into consideration and simplified into a coding form to test the two hypotheses. Variables such as themes of advertisement, age, published days, messages espoused, alcohol types, and types of advertisements have been independently tested for correlation. The research has highlighted that advertisers tend to promote alcohol as a form of reinforcing different cultures with the sales of alcohol. Also, there have been frequent reported attempts to magnify use of alcohol during weekends for tranquility from rigid bureaucratic norms. Waves of global cultures have also been associated with alcohol promotion as means of celebration Int. J. Soc. Sc. Manage. Vol. 8, Issue-3: 408-415.